Essentially Leading Antibody Production: An Investigation of Amino Acids, Myeloma, and Natural V-Region Signal Peptides in Producing Pertuzumab and Trastuzumab Variants - Ling, Wei-Li; Su, Chinh Tran-To; Lua, Wai-Heng; Poh, Jun-Jie; Ng, Yuen-Ling; Wipat, Anil; Gan, Samuel Ken-En (Frontiers in Immunology, 2020)
Boosting the production of recombinant therapeutic antibodies is crucial in both academic and industry settings. In this work, we investigated the usage of varying signal peptides by antibody genes and their roles in recombinant transient production. Comparing myeloma and the native signal peptides of both heavy and light chains in 168 antibody permutation variants, we performed a systematic analysis, finding amino acids counts to be involved in antibody production to construct a model for predicting co-transfection transient recombinant antibody production rates using the HEK293 system. The findings also provide insights into the usage of the large repertoire of antibody signal peptides.